2022
DOI: 10.3390/land11060887
|View full text |Cite
|
Sign up to set email alerts
|

The Boar War: Five Hot Factors Unleashing Boar Expansion and Related Emergency

Abstract: The recent and ever-growing problem of boar (Sus scrofa forms including wild boar, hybrid and feral pig) expansion is a very complex issue in wildlife management. The damages caused to biodiversity and the economies are addressed in different ways by the various countries, but research is needed to shed light on the causal factors of this emergency before defining a useful collaborative management policy. In this review, we screened more than 280 references published between 1975–2022, identifying and dealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 265 publications
0
23
0
Order By: Relevance
“…Consequently, it is not surprising that untested wild boar meat is responsible for 55% of global cases of human trichinellosis [ 28 ], being also implicated in several outbreaks of infection in European countries in the last decades [ [12] , [13] , [14] , [15] , [16] ]. The data above, combined to the increased consumption of wild boar meat in Europe [ 29 ], emphasize the crucial role of public health stakeholders in trichinellosis educational and surveillance programs towards hunters and consumers to prevent the risk of infection, as recommended by the European Regulation EC No 853/2004 [ 17 ] and the Commission Implementing Regulation EU 2015/1375 and 2019/627 [ 10 , 11 ]. In addition, the higher average of larvae in wild boars (i.e., 28.4 lpg) compared to other wildlife, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is not surprising that untested wild boar meat is responsible for 55% of global cases of human trichinellosis [ 28 ], being also implicated in several outbreaks of infection in European countries in the last decades [ [12] , [13] , [14] , [15] , [16] ]. The data above, combined to the increased consumption of wild boar meat in Europe [ 29 ], emphasize the crucial role of public health stakeholders in trichinellosis educational and surveillance programs towards hunters and consumers to prevent the risk of infection, as recommended by the European Regulation EC No 853/2004 [ 17 ] and the Commission Implementing Regulation EU 2015/1375 and 2019/627 [ 10 , 11 ]. In addition, the higher average of larvae in wild boars (i.e., 28.4 lpg) compared to other wildlife, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review conducted by Fulgione and Buglione [66] identified, on a global level, five significant factors that have transformed the wild boar and human conflict into an emergency. These are climate change, human-induced habitat modifications, predator regulation of the prey, hybridization with domestic forms and transfaunation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of wild boars in the transmission and persistence of African swine fever (ASF) is of growing concern in both Europe and Asia (Dixon et al 2020). Controlling wild boar populations has therefore become an even more urgent priority (Vicente et al 2019, Fulgione and Buglione 2022), and understanding factors limiting populations is crucial when aiming to limit the expanding wild boar distribution (Palencia et al 2023).…”
Section: Introductionmentioning
confidence: 99%